Penyelesaian Tindak Pidana Secara Diversi terhadap Anak di Wilayah Hukum Kepolisian Resort Langkat - Megayani Umry (Jurnal SOMASI (Sosial Humaniora Komunikasi), 2020)
During the last 2 years there has only been 1 (one) case where efforts were made to diversion, namely LP / 497 / IX / 2020 / SU / LKT 24 September 2020 committed theft of oil palm on plantation land in violation of Article 111 Subs Article 107 letter d of Law Number 39 2014 concerning Plantation. The theft was carried out by the perpetrator taking 15 (fifteen) palm fruit bunches weighing approximately 225 Kilograms (Kg) from the area of the reporter's plantation. However, this is an agreement to do diversion. Based on the background description above, it is interesting to conduct research in this thesis with the title: "Diversion settlement of criminal acts against children in the Legal Area of the Langkat Police Resort". Based on the foregoing, it can be seen that some of the problems that will be examined are what are the factors that influence the application of diversion to juvenile offenses in the area of Langkat Resort Police Law? The results of this research are the factors that influence the application of diversion to juvenile offenses. In the jurisdiction of the Langkat Resort Police, based on the explanation from Mr.Nelson Manurung, among them is a legal substance in which diversion attempts can indeed be made against any criminal act, but the condition is that the criminal act must be punishable by a criminal under 7 (seven) years and not a repetition of the crime The victim's revenge factor for the actions committed by the reported party because they have suffered material losses for the reported actions. The quality factor of law enforcement officers is related to the importance of diversion in the juvenile criminal justice system, and the legal culture factor.